Laparoscopic approach as a safe and effective option for incarcerated femoral hernias. Issue 2 (8th November 2021) - Okazaki, Ryo; Poudel, Saseem; Hane, Yuma; Saito, Takahiro; Muto, Jun; Syoji, Yasuhito; Hase, Ryunosuke; Senmaru, Naoto; Hirano, Satoshi
Abstract: Introduction: The laparoscopic approach for elective femoral herniorrhaphy is well established. However, femoral hernias often present as incarcerations and require emergency repair surgery, mainly using the open approach. This study aimed to retrospectively analyze the efficacy of the laparoscopic approach for incarcerated femoral hernias. Methods: Data of patients who underwent emergency surgery for incarcerated femoral hernia between April 2016 and August 2021 were retrospectively analyzed. Laparoscopy was performed whenever possible; however, conversion to an open approach remained a fallback option for when laparoscopic repair was not possible. In laparoscopic repair, incarcerated femoral hernias reduced using traction, water pressure, and preperitoneal methods. Data of patients who underwent open repair and laparoscopy were then compared. Results: During the observation period, 20 patients underwent emergency surgery for incarcerated femoral hernia. Eleven patients subsequently underwent repair using a laparoscopic approach, and eight underwent repair using an open approach. Only one patient underwent intestinal resection without hernia repair due to perforated bowel. Operative time for laparoscopic repair was longer. Mesh repair was performed in 18 patients. Four patients each in the laparoscopic repair and open group required intestinal resection. Conclusion: Incarcerated femoral hernias can be safely repaired using the laparoscopic approach.